Islamic approach on public awareness campaign of solid waste management / Affendi Ismail - Ismail, Affendi (Academy of Contemporary Islamic Studies (ACIS), 2016)
Drastic increase in solid waste has become one of the serious environmental problems in many parts of the world. Malaysia is also facing a similar problem with the uncontrolled amount of waste and low-quality management. Current awareness campaigns are not effective to change the attitude of the public. This study aimed to identify the attitude and acceptance of the Muslim community towards the Islamic approach in public awareness campaign of solid waste management. The content of current campaign, the media used and the slogan were also studied. A survey was conducted among 520 respondents who were randomly selected from the urban, suburban and rural areas of Kelantan. The results demonstrated that the current public awareness campaign is moderate and media campaigns failed to serve the purpose. Meanwhile, the attitude and acceptance of the respondents towards an Islamic- approach campaign is high. Respondents also showed a positive reaction towards the use of Islamic media channel and the slogan based on Islamic principles is considered effective. This study recommended for stakeholders and policy-makers to consider the role of religion (Islam) in designing a more effective awareness campaign among Muslims.